Health Care Expenditures and Longevity: Is there a Eubie Blake Effect? - Friedrich Breyer; Normann Lorenz; Thomas Niebel (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2012)
It is still an open question whether increasing life expectancy as such is causing higher health care expenditures (HCE). According to the red-herring-hypothesis, the positive correlation between age and HCE is exclusively due to the fact that mortality rises with age and a large share of HCE is caused by proximity to death. As a consequence, rising longevity through falling mortality rates may even reduce HCE. However, a weakness of previous empirical studies is that they use cross-sectional evidence to make inferences on a development over time. In this paper we try to isolate the impact of rising longevity on the trend of HCE over time by using data for a pseudo-panel of German sickness fund members over the period 1997-2009. Using dynamic panel data models, we find that age, mortality rate and five-year survival rates have a positive impact on per-capita HCE. Our explanation for the last finding is that physicians treat patients more aggressively if they think the result will pay off for a longer time span, which we call Eubie Blake effect. A simulation on the basis of an official population forecast for Germany is used to isolate the effect of demographic ageing on real per-capita HCE over the next decades.
Keywords: H51; J11; I19; 330; health care expenditures; ageing; longevity; 5-year survival rate